Why should majority voting be unfair? - Breitmoser, Yves; Tan, Jonathan H.W. (Elsevier, 2017)
The common use of majority rule in group decision making is puzzling. In theory, it inequitably favors the proposer, and paradoxically, it disadvantages voters further if they are inequity averse. In practice, however, outcomes are equitable. The present paper analyzes data from a novel experimental design to identify the underlying social preferences. Our experiment compares one-shot and indefinite horizon versions of random-proposer majority bargaining (the Baron-Ferejohn game) which allow us to disentangle behaviors compatible with altruism, inequity aversion, and reference dependent altruism. Most subjects are classified as reference-dependent altruists, around 10% are inequity averse. Subjects are egoistic when their payoff is below their reference point, they become efficiency concerned when satisfied, and the reference point is either the ex ante expectation or the opponent's payoff. Finally, we successfully test RDA out-of-sample on a number of distribution and bargaining games from three seminal social preference experiments.